KEMAMPUAN BERTANYA GURU DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS KURIKULUM MERDEKA DI SDN 2 MASBAGIK TIMUR: Penelitian Deskriptif - Muh. Genda Surya R.; A. Hari Witono; Johan Mahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to find out the extent of teachers' ability to implement the ability to ask questions in Indonesian learning based on the independent curriculum of State Elementary School 2 Masbagik Timur. This study uses a qualitative approach with a descriptive type of research. In this study, the data collection techniques used are interviews, observations, and documentation. The collected data is analyzed through data condensation, data presentation, and conclusion drawn. The results of the study showed that the teacher's questioning ability in learning Indonesian based on the independent curriculum at SDN 02 Masbagik Timur was still uneven, the observation results showed that teachers only carried out some aspects in questioning skills, aspects of questioning, especially advanced questioning, still need to be improved, besides that most teachers do not know the purpose and main function of questions. They only know questions only as intermediaries to find out the extent of students' understanding and are used only to attract students' attention. Lack of understanding and knowledge results in asking questions not to be considered in the teaching and learning process in the classroom, of course, these various shortcomings result in a less optimal teaching and learning process and the non-implementation of the desired learning objectives.